Association between Anemia and Severe Pneumonia among Children 6-59 Months Old in RSUD Wangaya, Denpasar: A Cross Sectional Study - Sukarno, Theodora; Suryawan, I Wayan Bikin; Sucipta, Anak Agung Made (Fakultas Kedokteran Universitas Pelita Harapan, 2023)
Background: Severe pneumonia dan anemia happened to many children under five years old. Anemia leads to hypercapnia and slowing down red blood cell maturation and facilitate ischaemic syndrome. In the other side, pneumonia may increase hepcidin that suppressed erythropoiesis, hence anemia could worsen pneumonia. The aim of this research is to find association of hemoglobin level and severe pneumonia under five years old.Methods: Cross sectional study was done in medical record RSUD Wangaya Denpasar starting from May-August 2022. Data was taken from subject with severe and mild and moderate pneumonia age 6-59 months old that admitted to PICU and Kaswari ward from January 2020-June 2022. Variables processed in this study are gender, pneumonia severity, hemoglobin level, and length of stayResult: This study admits 56 subjects that fulfilled inclusion and exclusion criteria. Boy and girls subjects are found equally (28 subjects equally in both groups). Severe pneumonia found in 18 (32.1%) subjects and 25 subjects (44.6%) has anemia. Length of stay for severe pneumonia is 4.83 ± 1.54 days. Hemoglobin level in severe pneumonia is 10.93±1,96 mg/dL and subjects with mild and moderate pneumonia is 11.69 ±1.41 mg/dL. The result of chi-square test between haemoglobin level and severe pneumonia is p= 0.26Conclusions: This study shows that there is no correlation between hemoglobin level and severe pneumonia. Further study is needed since the correlation between them is still controversial.